(untitled) (AYUSHDHARA, 2024)
Ayurveda is not only a medical science it is a holistic science of life. The aim of Ayurveda is promoting and preserving the health of individual and to cure from diseases. Pathyas are food substance and lifestyle of Ayurveda management line. Those drugs and regimes which are not harmful to channels and please the mind are considered as Pathya, and Sadapathya dravyas are such food which are good for most of the healthy individuals. Wholesome diet or Pathya plays equal role in management of any disease, it is essential to follow dietetic rules and regimes in order to curing diseases so that keep their Dhatu in a healthy state and will not let them get vitiated more from Doshas. The food which is prescribed according to disease by physician plays important role in successful treatment and it’s also prescribed as prophylactic and interventional diet. The concepts of Pathya and Apathya ahara vihara (diet and lifestyle) are still relevant and significant in the modern period as they offer a holistic approach to health, disease prevention, immunity boosting, and personalized care based on Ayurvedic principles.